Snacking Is Not Just Hunger: Do Emotional Eating and Gender Associated with Snacking Habits? - Syifa Raihani Lubis; Anna Undarwati (Journal of Educational, Health and Community Psychology, 2026)
The prevalence of unhealthy snacking behavior in Indonesia remains high and has the potential to increase the risk of non-communicable diseases such as obesity, chronic kidney disease, and cardiovascular disease. Therefore, it is important to identify the factors associated with  snacking habits. This study aims to determine whether emotional eating and gender are associated with snacking habits. The method used was a cross-sectional design with purposive sampling. A 280 participants aged 20-55 years were involved. The research instruments consisted of a demographic questionnaire, the Dutch Eating Behavior Questionnaire (DEBQ), and the Self Report Habit Index (SRHI), and data analysis was performed using the Univariat GLM test. The results showed that there was a significant interaction effect of emotional eating and gender on snacking habits (p<0.05). Women were found to have higher snacking habits than men. Thus, it is important to focus more on targeting women, especially those with emotional eating tendencies, in order to raise awareness of healthier diets.